Implementasi Metode Granada dalam Penerjemahan Al- Qur’an (Studi di Panti Asuhan Putra Mulia Jakarta Timur) - Ismail Ibrahim Ibnu Yassin; Supriyanto . (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2011)
Granada method as one method of translating the Qur'an that exists in the community has an important role in improving human resources (HR). Granada methods not only provide knowledge and technical skills but far more important to inculcate moral values and their application in every day, because once they understand the methods of Granada will be able to understand the meaning of the verses they read. The study of this thesis formulates three main issues as follows: 1). How is the implementation of Granada in the learning method of translation of the Qur'an. 2). How cans the effectiveness of Granada in the learning method of translation of the Qur'an. 3). What factors that support and hinder the implementation of the method of Granada. The purpose of this study is: 1). To know the implementation of Granada in the learning method of translation of the Qur'an. 2). Methods To determine the effectiveness of Granada in learning the Quran translator 3). To find the supporting factors and obstacles in the implementation of Granada method in studying the translator of the Qur'an. The research methods used in the preparation of this paper is to use Qualitative Methods Naturalistic, a method that produces descriptive data. The data obtained from the manuscripts, interviews, field notes, photographs, tape recorders, and other official documents. As for things that support the implementation of Granada method is: First, teachers who oversee the learning process are the ones who truly understand the Arabic language. Because the teachers are recruited from graduates of Granada Method LIPIA (Indonesian Institute of Education Sciences Arabia) and graduate school and alumni of the training method of Granada. Second, participants assisted with the module and VCD tutorial that summarizes all the material that will be studied. Third, the method is very short and compact so it does not beat around the bush so it takes a long time. Fourth, the spirit wants to know who so profoundly from the participants. And the Fifth, the delivery of a varied pattern. In general, obstacles often faced by the participants is difficult to adapt to this method at the beginning of the meeting, especially for those who have never previously knew Arabic, and at the time of writing memorized study abroad (dictation)